IDENTIFYING THE DIMENSIONS OF PERCEIVED CONSTRAINTS IN THE ADOPTION OF THE INTEGRATED FISH FARMING SYSTEM (IITM Journal of Business Studies, 2025)
Regardless of the Integrated Fish Farming System  (IFFS) being more economical and sustainable,  its adoption has not been commendable,  especially in developing countries like India.  In light of these concerns, the current study  attempts to understand the barriers to the  adoption of IFFS. In addition to the variables  of constraints identified through previous  literature, other variables were identified and  selected by conducting FGDs with experts  from the College of Fisheries, Raha, Assam. A  total of 504 farmers were chosen for the study  using multi-stage sampling approaches in  twelve districts that included all six of Assam’s  Agro-Climatic Zones. Analyzing the data with  SPSS, both descriptive and inferential statistics  were employed in comprehending the data. To  reduce the dimensions of restrictions, Principal  Component Analysis (PCA) was used in  conjunction with Exploratory Factor Analysis  (EFA). Using varimax rotation, the Factor  Analysis Model resulted in seven factors of  constraints. The model has been found to have  a good fit with an acceptable non-residual value.  The assessment of such constraints does not  only provide a helping hand in disseminating  such sustainable agricultural practices but also  ensures the sustainable usage of farm waste by  making ecological considerations.
Keywords: Perceived Constraints in Adoption; Agro-Climatic Zones of Assam; Integrated Farming System; Integrated Fish Farming System; Sustainability